Challenges Faced by Visually Impaired Teachers Working in Blind Schools in Online Teaching During Covid 19 - Zuber, Mohd.; Jamuna, R.; Muthmainnah, Muthmainnah (Yayasan Corolla Education Centre, 2021)
This study aims to examine the isssues in translating cultural terms between English and Malay. Thus, the researcher will thoroughly introduce the issue and analyse the findings by collecting data from books, conversation and social media, making this research a qualitative research. Thus, this research paper seeks to find a practical and professional solution for translators who are having the same issues whilst translating. In addition to that, the researcher has used Mona Baker’s equivalence typology to help complete this research.